Ultrasound Imaging in Psoriatic Arthritis: What Have We Learnt in the Last Five Years? - Dubash, Sayam R.; De Marco, Gabriele; Wakefield, Richard J.; Tan, Ai Lyn; McGonagle, Dennis; Marzo-Ortega, Helena (Frontiers in Medicine, 2020)
Psoriatic arthritis (PsA) is a complex heterogeneous disease with multiple inter-related pathologies such as synovitis, enthesitis, tendinopathy, and dactylitis. Clinical assessment is limited in its detail to assess pathology, thus in recent years, ultrasound (US) has become more popular, given its high sensitivity to detect inflammatory arthritis and ability to inform clinical decisions. Although a qualitative technique, US findings can be graded semi-quantitatively for grayscale (GS) and power Doppler (PD). Synovitis is frequently present in inflammatory arthritis pathologies, and in PsA, recent evidence shows a propensity for tendon and entheseal lesions. The presence of flexor tenosynovitis and flexor tendon insertional enthesopathy at accessory pulleys is supportive of the “Deep Koebner” concept. Peri-tendinous inflammation - mutual to PsA or rheumatoid arthritis (RA), is associated with soft tissue oedema with PD signal frequently at the flexor tendon compartments in PsA. Research on enthesitis in PsA/PsO has improved understanding in subclinical and clinical PsA, explored associations with progression to PsA, and investigated links to prognosis assessment. Dactylitis is a pathognomonic PsA lesion where US has enhanced knowledge of the disease course and pathology of lesions such as: flexor tenosynovitis; synovitis; and soft tissue oedema. Increased US sensitivity has also brought innovation including promising automated ultrasound scanning techniques. So, what have we learnt in recent years and what are the unmet needs to focus future research initiatives in this disabling disease? This narrative review article assesses the neoteric evidence, bringing into context the knowledge gained and highlighting potential areas of research.